Unique bonding pattern and resulting bond stretch isomerism in Be32−. Issue 7 (20th January 2015) - Goswami, Tamal; Paul, Satadal; Mandal, Subhajit; Misra, Anirban; Anoop, Anakuthil; Chattaraj, Pratim K.
<x xml:space="preserve">Abstract</x> The bond‐stretch isomers are characterized by a principal change in the bond‐length with the rest of the molecule being unaltered. The electronic structure regulates the bond stretch isomerism phenomenon in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3xrxz8hq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Be32−</alternatives> which has been investigated with density functional theory, ab initio CASSCF, highly efficient n‐electron valence state perturbation theory and multireference configuration interaction calculations. Two isomers are distinguished on different potential energy surfaces and the corresponding avoided crossing is also studied in details. The bonding pattern in two isomers are analysed through adaptive natural density partitioning analysis and quantum theory of atoms in molecules analysis. The bonds in both the isomers primarily involve the 2p orbitals, which overlap face‐to‐face in long‐bond isomer. Whereas, in‐plane π‐bonding occurs at the short‐bond isomer leading to unusual bent bond. © 2015 Wiley Periodicals, Inc.